A high-strength and high-plasticity titanium alloy processing technology
By performing high-temperature solution treatment after low-temperature aging of titanium alloy, the fine sheet layer αs is stabilized and a large number of fine isometric αp is formed, which solves the problem of difficulty in simultaneously improving the strength and plasticity of titanium alloy in the prior art, and achieves the simultaneous improvement of material properties.
Patent Information
- Application Number
- CN202410333471.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-22
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-03-22
AI Technical Summary
The prior art is difficult to simultaneously improve the strength and plasticity of titanium alloys, and the improvement of material performance is limited.
By adding high-temperature solution treatment after low-temperature aging, the fine sheet layer αs is stabilized, thereby forming a large number of fine equiaxed αp in the subsequent process, achieving simultaneous improvement of strength and plasticity.
This process can effectively improve the strength and plasticity of titanium alloy, and has high feasibility, low cost, and better tissue uniformity during processing and forming.
Smart Images

Figure CN118291896B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium alloy forging preparation technology, and in particular to a high-strength and high-plasticity titanium alloy processing technology. Background Art
[0002] Titanium alloys have high specific strength, good ductility and good fracture toughness, and their market share in the aerospace field is increasing. The strength and plasticity of titanium alloys depend largely on their microstructure. The most common two-phase titanium alloy structure is composed of equiaxed primary α phase (αp), secondary α lamellae (αs) and β matrix, among which equiaxed αp is conducive to improving plasticity, and lamellae αs are conducive to improving strength. At present, during the aging heat treatment of the alloy, a large number of fine α lamellae (αs) can be precipitated in the β matrix, which improves the strength of the alloy. However, when the alloy is aged to a high strength level, the equiaxed αp is softer than the lamellae αs, resulting in uneven deformation of each component and fracture, which ultimately causes the plasticity of the material to decrease. Therefore, in order to obtain a better strength-plasticity combination, it is necessary to modulate the dual-state structure morphology.
[0003] Since the lamellar αs can be effectively adjusted by adjusting the heat treatment temperature, and the equiaxed αp is produced by forging, the amount of αp is fixed after forging, and the aging treatment can only adjust the shape and size of αp but cannot change the amount. In order to improve the plasticity and strength of the alloy, the conventional method in the prior art is to increase or decrease the lamellar αs strength by adjusting the aging temperature, for example, adjusting the aging temperature within the range of 590-650°C to increase or decrease the overall strength of the material. At the same time, it will reduce or increase the plasticity of the material, and cannot achieve simultaneous improvement of strength and plasticity, and the improvement of material performance is limited. Summary of the invention
[0004] The present invention aims to provide a high-strength and high-plasticity titanium alloy processing technology to solve the problem in the prior art that it is difficult to simultaneously improve the strength and plasticity of titanium alloys during processing.
[0005] When the inventors were thinking about how to improve the strength and plasticity of the alloy, they referred to the solutions in the prior art. They found that the strength and plasticity differences between the two phases can be reduced by refining the equiaxed αp and coarsening the lamellar αs, thereby effectively improving the performance match and ultimately improving the strength and plasticity of the material at the same time. However, in the actual forging process, the equiaxed αp is very difficult to break during forging refinement. Generally, it is necessary to perform severe deformation at a temperature 30°C to 100°C lower than the conventional forging temperature to complete partial crushing. This requires high forging capacity of the equipment, and has the disadvantages of high energy loss and high grinding loss, so its practical application is very limited. Therefore, it is necessary to further explore the forging process in the prior art to achieve the simultaneous improvement of the plasticity and strength of the material.
[0006] The inventors analyzed the mechanism of improving the forging performance of titanium alloys in the prior art and believed that the strength of two-phase titanium alloys mainly depends on the average maximum strength of the two phases, while the plasticity depends on the difference between the maximum strengths of the two phases. Therefore, the inventors believe that by increasing αp, both strength and plasticity can be effectively improved. In the evolution of the α phase, the equiaxed αp is transformed from the lamellar αs generated during the cooling of the single-phase region and the heating of the two-phase region through growth and spheroidization. Therefore, by changing the size of the lamellar αs, the size of αp after the αs transformation can be changed.
[0007] According to the precipitation law of titanium alloy phase, the lower the temperature, the greater the degree of supercooling, the slower the atomic diffusion, and the finer the precipitated lamellar αs. Therefore, a large number of very fine lamellar αs can be precipitated by low temperature, so that a large number of αp can be obtained in the subsequent α phase evolution process, so as to improve the plasticity and strength of the alloy at the same time. According to this method, it is less difficult than forging to refine αp, and the effect is better. Furthermore, although a large number of very fine lamellar αs can be precipitated by low temperature, the fine lamellar αs is prone to dynamic dissolution and growth when it returns to the high temperature zone for heating and forging, causing the fine lamellar αs to be transformed into a small and large lamellar αs, which in turn affects the subsequent αs growth spheroidization and transformation into the size of αp, thereby affecting the plasticity of the alloy.
[0008] In response to the problem of dynamic dissolution and growth of lamellar αs during heating and forging in high-temperature zones, the inventors' research and development idea is to use technical means to keep the lamellar αs as fine as possible. Therefore, the inventors further optimized and improved the technical solution, and finally adopted the method of increasing high-temperature solid solution after low-temperature aging and before forging to stabilize the fine lamellar αs, thereby ultimately achieving the transformation of a large number of fine αs into a large number of fine equiaxed αp, thereby improving the strength and plasticity of the alloy at the same time.
[0009] In order to solve the problems in the background technology and realize the above-mentioned solution, the present invention adopts the following technical solution: a high-strength and high-plasticity titanium alloy processing technology, comprising the following steps:
[0010] S1, single-phase solid solution forging, heating the blank to the single-phase temperature T1 and then keeping it warm, then forging and cooling;
[0011] S2, low temperature aging, the billet cooled after forging in S1 is placed at a temperature T2 below the phase transition point for low temperature aging treatment, then heated to a temperature T3 close to the phase transition point for high temperature solution treatment, and then cooled;
[0012] S3, the billet cooled in S2 is subsequently forged to finally obtain a forging.
[0013] The principle of this scheme is: in this application, forging is first carried out within the temperature range of the single-phase region, and low-temperature aging treatment is carried out after cooling. Since the temperature T2 of the low-temperature aging treatment is in a low-temperature state below the phase transition point temperature, a large number of very fine lamellar layers αs can be precipitated at low temperatures, and then the blank is subjected to a temperature-raising treatment, and the temperature is raised to a temperature T3 close to the phase transition point temperature, and a high-temperature solid solution is carried out to stabilize the precipitated lamellar layers αs, so that they remain in a large number and small state, and then after heat preservation, the lamellar layers αs are partially transformed into equiaxed αp. Since the number of αs is large and small, the number of αp obtained by the transformation is also large and small. While improving the strength of the alloy material, the plasticity of the alloy can also be effectively improved, thereby achieving a simultaneous improvement in the strength and plasticity of the alloy material.
[0014] The beneficial effects of this program are:
[0015] 1. High process feasibility: Compared with the prior art, when the strength of the alloy material is increased / decreased, the plasticity of the alloy material will be increased / decreased, and the strength and plasticity of the alloy material cannot be improved at the same time. In this application, a low-temperature aging method is set up to precipitate a large number of fine lamellar layers αs at low temperature, and finally a large number of fine equiaxed αp are obtained, which can simultaneously improve the strength and plasticity of the alloy. Moreover, the technical solution of this application is adopted. Compared with the process of obtaining fine αp by low-temperature large deformation forging, the process steps of this application are fewer, the cost is lower, and the uniformity of the processed structure is better.
[0016] 2. A large number of fine αp can be obtained to enhance the plasticity of the alloy material: In the present application, high-temperature solid solution is carried out immediately after low-temperature aging, which can effectively reduce the dynamic dissolution and growth of the lamellar αs precipitated during low-temperature aging, thereby keeping the lamellar αs in a fine state, so that a large number of fine αp can be precipitated in the subsequent process, effectively improving the plasticity of the alloy material, and combined with the subsequent forging, the plasticity and strength of the alloy material are improved.
[0017] Preferably, as an improvement, the aging temperature T2 in the low-temperature aging in S2 is in the range of 350 to 550°C.
[0018] In this scheme, the low-temperature aging temperature of S2 is controlled at 350-550°C, which can avoid the situation where the solid-state phase transformation cannot occur due to too low temperature, and can also avoid the situation where the temperature is too high and a large number of fine lamellar αs cannot be precipitated. By controlling the low-temperature aging temperature within the range of 350-550°C, a large number of fine lamellar αs can be precipitated, thereby generating a large number of fine αp in the subsequent process, effectively improving the plasticity of the alloy.
[0019] Preferably, as an improvement, the low-temperature aging time t2 in S2 is (m / T2), expressed in minutes, wherein T2 is the temperature value of the low-temperature aging, and the coefficient m ranges from 150,000 to 300,000.
[0020] In this scheme, the low-temperature aging time is determined according to the low-temperature aging temperature T2, and the coefficient m is set at 150000-300000, which can ensure that the low-temperature aging has a good effect, that is, a large number of lamellae αs can be precipitated.
[0021] Preferably, as an improvement, the temperature value T3 of the high temperature solid solution after aging treatment in S2 is T β -(20~40)℃.
[0022] In this scheme, the temperature range of high-temperature solid solution is set to a high temperature state of 20 to 40° C. below the phase transition temperature, so that the fine flake layer αs is stably retained to facilitate the subsequent generation of fine αp.
[0023] Preferably, as an improvement, the holding time t3 of the high temperature solution in S2 is (0.3-0.5) × D, in minutes, wherein D is the minimum value of the diameter or thickness of the billet, in mm.
[0024] In this solution, the holding time of the high-temperature solid solution of the billet is determined according to the minimum value of the billet diameter or thickness value, so as to effectively ensure the effect of the high-temperature solid solution.
[0025] Preferably, as an improvement, the single-phase zone insulation temperature T1 in S1 = T β +(30~80)℃.
[0026] In this scheme, the temperature of the blank is heated to 30 to 80° C. higher than the phase change temperature to facilitate forging processing.
[0027] Preferably, as an improvement, the single-phase region holding time in S1 is t1=(0.5-1)×D, in minutes, where D is the minimum value of the diameter or thickness of the billet, in mm.
[0028] In this solution, the single-phase zone insulation time t1 is determined by the size of the billet, so that the billet is heated thoroughly, which is convenient for subsequent forging.
[0029] Preferably, as an improvement, the aging temperature T2 in the low-temperature aging in S2 is equal to 400°C.
[0030] In this scheme, the temperature value in the low-temperature aging is set to 400°C. At this temperature value, a large number of fine lamellae αs can be obtained. Compared with other temperature values, the number of lamellae αs obtained is the largest and the smallest, which can achieve the best effect.
[0031] Preferably, as an improvement, the cooling after forging in S1 is air cooling, and the cooling in S2 is water cooling.
[0032] In this scheme, air cooling is used after forging in S1 to slowly cool the billet, while water cooling is used in S2 to obtain a large number of fine and stable lamellar layers αs.
[0033] Preferably, as an improvement, the subsequent forging in S3 includes one or more combinations of flat square forging, reversing forging or upsetting.
[0034] In this solution, the subsequent forging adopts conventional titanium alloy heating forging to finally obtain an alloy material with high strength and high plasticity. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a lamellae tissue morphology diagram of Example 1.
[0036] Figure 2 This is a high-magnification microstructure image of the finished product of Example 1.
[0037] Figure 3 This is the lamellae organization morphology of comparative example 1.
[0038] Figure 4 This is the lamellae organization morphology of comparative example 2.
[0039] Figure 5 This is a high-magnification microstructure image of the finished product of comparative example three.
[0040] Figure 6 This is a high-magnification microstructure image of the finished product of Comparative Example 4. DETAILED DESCRIPTION
[0041] The following is further described in detail through specific implementation methods:
[0042] A high-strength and high-plasticity titanium alloy processing process comprises the following steps:
[0043] S1, single-phase solid solution forging, first heat the billet to the single-phase temperature T1, T1 = T β + (30 ~ 80) ℃, that is, the rising temperature value is higher than the phase change point by 30 ~ 80 ℃, and then the heat preservation is carried out, and the heat preservation time t1 = (0.5 ~ 1) × D, where D is the minimum value of the diameter or thickness of the billet, in mm; when the heat preservation is completed, forging is carried out, and air cooling is used after forging.
[0044] S2, low temperature aging, the billet after air cooling in S1 is placed in a temperature environment T2 below the phase transition point temperature for low temperature aging treatment, wherein the temperature range of T2 is 350-550°C, preferably, the temperature T2 of low temperature aging is set to 400°C, the time of low temperature aging is t2=(m / T2), the unit is minute, wherein T2 is the temperature value of low temperature aging, and the coefficient m ranges from 150000 to 300000 within this temperature range; after the low temperature aging is completed, the billet is heated to a temperature close to the phase transition point T3 for high temperature solution treatment, T3= T β - (20~40) ℃, that is, the temperature of the billet is raised to a high temperature state of 20~40℃ below the phase transformation point, and then the high temperature solution time t3 = (0.3~0.5) × D, the unit is minutes, where D is the minimum value of the diameter or thickness of the billet, the unit is mm; after the high temperature solution, water cooling is used for cooling.
[0045] In this step, a large number of fine lamellar αs can be precipitated in the billet through low-temperature aging, creating conditions for the growth and spheroidization of αs to transform into αp during subsequent single-phase zone cooling and two-phase zone heating. At the same time, in this step, the billet is subjected to high-temperature solid solution after low-temperature aging, and the precipitated fine lamellar αs is stabilized by high-temperature solid solution, thereby reducing the dynamic dissolution and growth of the subsequent billet when it is returned to the high-temperature zone for heating and forging, resulting in a reduction in the lamellar αs and an increase in volume, which affects the final number and size of αp and fails to enhance the strength of the alloy.
[0046] S3. The billet after water cooling in S2 is subjected to subsequent forging. The specific form of the subsequent forging is one or more combinations of flat square forging, reversing forging or upsetting, and the subsequent forging is used to obtain high-strength and high-plasticity alloy forgings.
[0047] In this embodiment, by setting low-temperature aging and high-temperature solid solution in S2, a large number of fine and stable lamellar αs can be precipitated in the billet, so that a large number of fine equiaxed αp can be formed in the subsequent forging in S3. In this way, while a large number of lamellar αs are obtained by conventional aging treatment in the prior art, the equiaxed αp is effectively improved, and ultimately the strength and plasticity of the alloy material are simultaneously improved.
[0048] In this embodiment, a typical two-phase titanium alloy TC17 is used as an example for explanation. The nominal composition of TC17 is Ti-5Al-4Mo-4Cr-2Sn-2Zr, and its phase transition point β transition temperature is 890° C. The process steps used are as follows:
[0049] Embodiment 1:
[0050] S1. Single-phase solid solution forging. The size of the billet is 200×200×400mmm. The billet is heated to the single-phase temperature T1 of 930℃. The insulation time is 2h. Then forging is carried out. The forging deformation is 30%. Air cooling is performed after forging.
[0051] S2, low temperature aging, the billet after air cooling in S1 is placed in a temperature environment of 400℃ for aging for 8h, and then high temperature solid solution is carried out to raise the billet temperature to 870℃, and then water-cooled after keeping it at this temperature for 1h;
[0052] S3, the subsequent forging was changed, and two upsetting and drawing were performed at a temperature of 850℃. The deformation of upsetting and drawing was 35%. Finally, the billet was drawn to 150×150×700mm to obtain a forging. A 150×150×30mm specimen was taken from the end of the forging for heat treatment and physical and chemical testing. The specimen heat treatment system was: 840℃ / 3h, air cooling + 800℃ / 4h, water cooling + 630℃ / 8h, air cooling; Figure 1 This is a lamella tissue morphology diagram of Example 1. Figure 2 This is a high-magnification microstructure image of the finished product of Example 1.
[0053] Comparative Example 1: Compared with Example 1, the difference between Comparative Example 1 is that the low-temperature aging temperature in Example 1 is 400°C, and the low-temperature aging temperature in Comparative Example 1 is 650°C, and the rest is the same. Figure 3 This is the lamellae organization morphology of comparative example 1.
[0054] Comparative Example 2: Compared with Example 1, the only difference between Comparative Example 2 is that the temperature of low-temperature aging in Example 1 is 400° C., while the temperature of low-temperature aging in Comparative Example 2 is 850° C., and the rest are the same. Figure 4 This is the lamellae organization morphology of comparative example 2.
[0055] Comparative Example 3: Compared with Example 1, the only difference of Comparative Example 3 is that Comparative Example 3 does not have S2, that is, low-temperature aging and high-temperature solution treatment processes are not provided. Figure 5 This is a high-magnification microstructure image of the finished product of comparative example 3.
[0056] Comparative Example 4: Compared with Example 1, the only difference of Comparative Example 4 is that no high-temperature solution treatment process is provided in S2 of Comparative Example 4. Figure 6 This is a high-magnification microstructure image of the finished product of comparative example 4.
[0057] By comparison Figure 1 , Figure 3 and Figure 4After low-temperature aging at 400°C, the size of the lamellar αs phase is about 0.8μm, and the number of lamellar αs is large and small. In comparison, when the aging temperature is 850°C, the number of lamellar αs is much smaller and the volume is much larger. Therefore, the low-temperature aging method can effectively increase the number of lamellar αs, and the obtained lamellar αs is in a small state, thereby obtaining a large number of small equiaxed αp in the subsequent process, creating favorable conditions for improving the plasticity of the alloy.
[0058] By comparison Figure 2 and Figure 5 The αp average diameter was measured by the diagonal measurement method, and the αp average diameter in Example 1 was 4.13 μm, the αp average diameter in Comparative Example 3 was 8.56 μm, and the αp average diameter in Comparative Example 4 was 6.73 μm. It can be seen that by using a processing technology of low-temperature aging combined with high-temperature solid solution, an αp alloy with obvious refinement can be obtained.
[0059] Embodiment 2:
[0060] The difference between Example 2 and Example 1 is that the heat treatment system of the sample in S3 of Example 2 is changed. The heat treatment system in this example is: 840℃ / 3h, air cooling+800℃ / 4h, water cooling+635℃ / 8h, air cooling.
[0061] Comparative Example 5:
[0062] The difference between Example 5 and Example 3 is that in Example 5, the heat treatment system of the sample in S3 is changed, and the heat treatment system in this embodiment is: 840℃ / 3h, air cooling+800℃ / 4h, water cooling+635℃ / 8h, air cooling.
[0063] Comparative Example 6:
[0064] The difference between Example 6 and Example 4 is that in Example 6, the heat treatment system of the sample in S3 is changed, and the heat treatment system in this embodiment is: 840℃ / 3h, air cooling+800℃ / 4h, water cooling+635℃ / 8h, air cooling.
[0065] The room temperature tensile test results of Example 1, Comparative Example 3, Comparative Example 4, Example 2, Comparative Example 5 and Comparative Example 6 are shown in Table 1:
[0066] Tensile strength Rm / MPa Yield strength Rp0.2 / MPa Elongation A / % Sectional shrinkage Z / % Embodiment 1 1253 1178 10.7 21.1 Comparative Example 3 1195 1134 11.0 20.4 Comparative Example 4 1205 1146 11.2 19.8 Embodiment 2 1235 1165 14.7 28.5 Comparative Example 5 1177 1120 14.6 26.8 Comparative Example 6 1188 1130 13.0 28.8
[0067] By comparing Comparative Example 3 and Comparative Example 5: By changing the temperature during ordinary aging, which is commonly used in the prior art to change the properties of titanium alloy), the aging temperature is increased. By comparing the test results of Comparative Example 3 and Comparative Example 5, the tensile strength and yield strength are both reduced, and the elongation and cross-sectional shrinkage are both increased, indicating that although the plasticity of the alloy material can be improved by adopting the form of ordinary heating, the strength of the alloy material will be reduced. When one of the properties, strength or plasticity, is improved, the other property cannot be maintained or improved.
[0068] By comparing Example 1 with Example 2: The difference between Example 1 and Example 2 is that the aging temperature of the subsequent heat treatment of S3 is changed, and the temperature is increased. By comparing the test results of Example 1 and Example 2, it is similar to the test results of Comparative Examples 3 and 4. Only by increasing the aging temperature of the heat treatment, when one of the plasticity or strength of the alloy material is improved, the other property will be reduced. For example, compared with Example 2, the plasticity of Example 1 is greatly enhanced, but the strength is reduced.
[0069] By comparing Example 1 with Comparative Example 3 and Comparative Example 4: The only difference between Example 1 and Comparative Example 3 is that S2 is added in Example 1, that is, low-temperature aging and high-temperature solid solution are added. Compared with Example 1, the only difference between Comparative Example 4 is that no high-temperature solid solution process is set in S2 of Comparative Example 4. By comparing the test results of Example 1 with Comparative Example 3 and Comparative Example 4, the results of tensile strength and yield strength are shown as Example 1>Comparative Example 4>Comparative Example 3, while the elongation of Example 1 is similar to the test results of Comparative Example 3 and Comparative Example 4, indicating that by adding two treatment processes of low-temperature aging and high-temperature solid solution to S2 in Example 1, the average strength of the material can be improved while the plasticity remains basically the same. When both processes are used, the increase is about 50MPa, achieving the improvement of the strength of the alloy without reducing the plasticity.
[0070] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A high-strength and high-plasticity titanium alloy processing process, characterized in that: The steps include: S1, single-phase solid solution forging, heat the billet to the single-phase temperature T1 and then keep it warm, the single-phase temperature T1 = T β + (30~80)℃, then forge and cool; S2, low temperature aging, the billet cooled after S1 forging is placed at T2 temperature below the phase transition point for low temperature aging treatment. The range of the aging temperature value T2 in the low temperature aging is 350-550℃, and then the temperature is raised to T3 close to the phase transition point for high temperature solution treatment. The temperature value of high temperature solution after aging treatment is T3 = T β - (20~40)℃, then cool down; S3, the billet cooled in S2 is subsequently forged to finally obtain a forging.
2. A high-strength and high-plasticity titanium alloy processing process according to claim 1, characterized in that: The time of low temperature aging in S2 is t2 = (m / T2), in minutes, where T2 is the temperature value of low temperature aging, and the coefficient m ranges from 150,000 to 300,000.
3. The high-strength and high-plasticity titanium alloy processing technology according to claim 1 is characterized in that: The holding time of high temperature solution in S2 is t3 = (0.3~0.5) × D, in minutes, where D is the minimum value of the diameter or thickness of the billet, in mm.
4. The high-strength and high-plasticity titanium alloy processing technology according to claim 1 is characterized in that: The single-phase zone holding time in S1 is t1 = (0.5~1) × D, in minutes, where D is the minimum value of the diameter or thickness of the billet, in mm.
5. The high-strength and high-plasticity titanium alloy processing technology according to claim 1 is characterized in that: The aging temperature T2 in the low temperature aging of S2 is equal to 400°C.
6. The high-strength and high-plasticity titanium alloy processing technology according to claim 1 is characterized in that: The cooling after forging in S1 is air cooling, and the cooling in S2 is water cooling.
7. The high-strength and high-plasticity titanium alloy processing technology according to claim 1 is characterized in that: The subsequent forging in S3 includes one or more combinations of flat square forging, reversing forging or upsetting.
Citation Information
Patent Citations
Titanium alloy heat treatment method and multi-scale polymorphic precipitated phase structure prepared through titanium alloy heat treatment method
CN115287561A